Kesiapan Belajar Siswa SD di Tinjau dari Kebiasaan Mandi Pagi - Nur Azizah; Ine Febrian Maharani; Muhammad Nofan Zulfahmi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The impact of morning bathing habits on the learning readiness of elementary school students using a literature review method. Data were collected from various reliable sources such as scientific journals, books, and relevant articles. The results showed that students who regularly bathe in the morning have higher learning readiness levels compared to those who do not. Morning bathing habits have been proven to enhance students’ concentration, enthusiasm, and motivation to learn. Therefore, morning bathing habits can be considered a strategy to improve elementary students’ readiness to learn.